The Influence of Perceived Functional, Emotional, and Social Value on Repurchase Intention of Skintific Products among Consumers in Samarinda City - Wahyu DwiJaya; Hudyah Astuti Sudirman; Istimaroh (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2025)
To analyze the influence of perceived functional, emotional, and social value on repurchase intention of Skintific products in Samarinda. Design/Methodology/Approach: Explanatory quantitative method with online questionnaires and multiple linear regression analysis of 73 active customers. Findings: Functional (β=0.421; p<0.001), emotional (β=0.200; p=0.036), and social value (β=0.426; p<0.001) significantly affect repurchase intention. Social value is most dominant. Collectively, these values explain 91.1% of repurchase intention variance (R²=0.911). Originality/Value: This study integrates three value dimensions holistically in the under-explored non-Java market, proving integrated strategies outperform partial approaches.